Colchicine-Mediated Polyploidization For Improvement Of French Marigold Traits - Aziz Nur Arifin; Parjanto; Endang Yuniastuti (International Journal of Interdisciplinary Research, 2026)
This study evaluated the effects of colchicine concentration and soaking duration on vegetative morphology of French marigold (Tagetes patula L.) cv. Janie Spry, a naturally allotetraploid species (2n = 4x = 48). A 4×3 factorial completely randomized design was employed with four colchicine concentrations (0%, 0.1%, 0.2%, 0.3%) and three soaking durations (4, 8, 12 hours), totaling 12 treatments with three replications (n = 36). Germinated seeds at the radicle stage were soaked in colchicine solutions and grown in a greenhouse. Survival rate, plant height, stem diameter, and number of shoots were recorded during the vegetative phase. Two-way ANOVA revealed highly significant interaction effects (p<0.001) of concentration and duration on survival rate and shoot number, while plant height and stem diameter were not significantly affected. Survival declined sharply at higher concentrations with prolonged soaking, reaching only 30% at 0.3% colchicine for 12 hours. The 0.2% colchicine at 4-hour soaking treatment was identified as optimal, maintaining 90% survival while increasing shoot number by 37.7% relative to the control (30.7 vs. 22.3 shoots plant⁻¹). The highest shoot count (34.3 shoots plant⁻¹) occurred at 0.3% for 12 hours but was accompanied by unacceptable seedling mortality. These results indicate that moderate colchicine concentrations with short exposure offer an effective balance between morphological modification and seedling viability in T. patula. Cytological confirmation and floral trait evaluation will be reported in a subsequent publication.